Development and application of relevance and reliability criteria for water treatment removal efficiencies of chemicals of emerging concern - Fischer, Astrid (2019)
With the growth in production and use of chemicals and the fact that many end up in the aquatic environment, there is an increasing need for advanced water treatment technologies that can remove chemicals of emerging concern (CECs) from water. The current lack of a homogenous approach for testing advanced water treatment technologies hampers the interpretation and evaluation of CEC removal efficiency data, and hinders informed decision making by stakeholders with regard to which treatment technology could satisfy their specific needs. Here a data evaluation framework is proposed to improve the use of current knowledge in the field of advanced water treatment technologies for drinking water and wastewater, consisting of a set of 9 relevance criteria and 51 reliability criteria. The two criteria sets underpin a thorough, unbiased and standardised method to select studies to evaluate and compare CEC removal efficiency of advanced water treatment technologies in a scientifically sound way. The relevance criteria set was applied to 244 papers on removal efficiency, of which only 20% fulfilled the criteria. The reliability criteria were applied to the remaining papers. In general these criteria were fulfilled with regards to information on the target compound, the water matrix and the treatment process conditions. However, there was a lack of information on data interpretation and statistics. In conclusion, a minority of the evaluated papers are suited for comparison across techniques, compounds and water matrixes. There is a clear need for more uniform reporting of water treatment studies for CEC removal. In the future this will benefit the selection of appropriate technologies.